IMPLEMENTATION OF THE EMERGENCY CURRICULUM ON THEMATIC LEARNING IN PRIVATE ELEMENTARY SCHOOL - Hani Hanifah; Seni Apriliya; Erwin Rahayu Saputra (Jurnal Elementary:Kajian Teori dan Hasil Penelitian Pendidikan Sekolah Dasar, 2022)
Abstract:  The Covid-19 pandemic has changed the order of the world of education, this has prompted the government to issue policy Number 719/P/2020 regarding guidelines for implementing the curriculum in educational units under special conditions. The research aims to determine the strategies, learning principles, and policy analysis of the emergency curriculum. The data collection techniques in this study were distributing questionnaires to 26 private elementary school teachers in Tasikmalaya City as participants. The research method used is the quantitative method and the data analysis technique used is descriptive analysis. The results of the study stated that the existence of an emergency curriculum policy in the conditions of the Covid-19 pandemic was effective in thematic learning in private elementary schools by using learning strategies that emphasize the character of students and the principles of active and fun learning.